QT Prolongation, Torsade de Pointes, Myocardial Ischemia From Coronary Vasospasm, and Headache Medications. Part 1: Review of Serotonergic Cardiac Adverse Events With a Triptan Case. Issue 1 (6th December 2012) - Stillman, Mark J.; Tepper, Stewart; Tepper, Deborah E.; Cho, Leslie
Abstract : Serotonin (5‐hydroxytryptamine)1 B /1 D agonists are vasoconstrictors that can affect coronary and cerebral arteries. Retrosternal chest, arm, and jaw pain following triptan use is generally attributed to "triptan sensations" and dismissed as noncardiac. However, triptans narrow normal coronary arteries and occasionally trigger vasospasm. They are contraindicated in atherosclerotic vascular disease. Part 1 of this review examines the relationship of medications used in migraine with the likelihood of causing vasospasm or vasoconstriction, and the triggering of cardiac arrhythmias. We report an illustrative case of polymorphic ventricular tachyarrhythmia, electrocardiogram changes consistent with cardiac ischemia, and acquired corrected QT interval lengthening following oral sumatriptan in a 53‐year‐old migraineur without risk factors for coronary artery disease (CAD). Extensive evaluation revealed insignificant single coronary vessel atherosclerosis and coronary artery vasospasm on ergonovine challenge. The report highlights the hidden risk that may underlie a "triptan sensation" and the possible association of the vasospastic features of Raynaud's phenomenon, migraine headaches, and coronary vasospasm. Part 1 discusses the risks for Torsade de Pointes, vasospasm, and ischemia, with a review and discussion of case reports of triptan‐associated cardiovascular events in migraineurs with and without CAD risk factors or documented CAD; of the epidemiology and studies of triptans, vasospasm, and cardiovascular morbidity; and of the relationship of variant angina, migraine, and vasospastic disease. In the second part of this review, headache medications and their propensity for corrected QT prolongation will be summarized.